2009
DOI: 10.1159/000209379
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Gelatinase-Associated Lipocalin as an Early Biomarker of Nephropathy in Diabetic Patients

Abstract: Background/Aims: Renal tubulointerstitium plays an important role in the development and progression of diabetic nephropathy. Methods: With the present study, we aimed at evaluating the levels of neutrophil gelatinase-associated lipocalin (NGAL), a tubular stress protein, in serum (sNGAL) and urine (uNGAL) from a cohort of 56 patients with type 2 diabetes mellitus categorized into three groups (normoalbuminuria, microalbuminuria and diabetic nephropathy). Results: All groups showed increased NGAL values with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
119
2
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(149 citation statements)
references
References 41 publications
20
119
2
8
Order By: Relevance
“…At baseline, progressors as well as their matched controls had more albuminuria than the overall cohort population. We and others have found that albuminuria is positively associated with the urinary excretion of markers indicating damage to the proximal tubule (37,38). This is corroborated in this study, because we found such an association in patients as well as controls (Table 4).…”
Section: Discussionsupporting
confidence: 92%
“…At baseline, progressors as well as their matched controls had more albuminuria than the overall cohort population. We and others have found that albuminuria is positively associated with the urinary excretion of markers indicating damage to the proximal tubule (37,38). This is corroborated in this study, because we found such an association in patients as well as controls (Table 4).…”
Section: Discussionsupporting
confidence: 92%
“…Biomarkers of AKI, such as NGAL, KIM‐1, and IL‐18, may be potentially beneficial for early detection, diagnosis, and prognosis of AKI after cardiac surgery 35, 36. However, in our study and others, these markers are commonly elevated at baseline, and thus a relatively large change from baseline (doubling or tripling) would be needed to detect AKI in this setting 37, 38, 39. In our study, the results in functional and novel injury markers were concordant in demonstrating no benefit of ABT‐719 treatment.…”
Section: Discussionmentioning
confidence: 66%
“…In patients with moderate kidney disease, serum and urine NGAL concentrations have been identified to be independent predictors of CKD progression [15]. Furthermore, urine NGAL can be used as an early biomarker of diabetic nephropathy [16]. However, urine NGAL was not found to be different between obese children and healthy controls in Goknar et al's study [11].…”
Section: Microalbuminuriamentioning
confidence: 95%